Impact of Bimanual Vaginal Examination on Pap Smear Test Results - Esengül Türkyılmaz; Melahat Yıldırım; Raziye Desdicioğlu; Huban Sibel Orhun Yavuz; Ayşe Filiz Yavuz Avşar (Medical Network, 2017)
Objective: The aim of the study is to evaluate the possible effects of the various conditions especially bimanual examination on the adequacy of pap smear test. Study Design: Presented here is a prospective controlled clinical trial carried out at Ankara Atatürk Training and Research Hospital between November 2013 and March 2014. Total of 1771 patients seen at the gynecology outpatient clinic were included in the study. The technique described by the American Society of Cytopathology Criteria 2000 for the preparation of the specimen was followed. Updated Bethesda system 2014 was used for reporting the results. Results: Number of subjects in smear before examination group was 1194 and in the smear after examination group was 577. Two percent (n=36 subjects) of the cervicovaginal report was inadequate. When other clinical conditions were not taken into consideration, the likelihood ratio for inadequate smear in the smear after examination group was 2.64 compared to smear before examination group (p=0,004). Conclusions: In some conditions cervicovaginal smear sampling may be carried out after bimanual vaginal examination instead of missing the chance to screen the women. However, the patients have to be informed that cervicovaginal smear result might be inadequate so that a repeat test has to be carried out.